Deciphering the Presence of Active Interscapular Brown Adipose Tissue in Humans - Sanchez‐Gomez, Joaquin; Ruiz‐Campos, Samuel; Chica‐Perez, Anabel; Baena‐Raya, Andrés; Acosta, Francisco M.; Wolfrum, Christian; Rensen, Patrick C. N.; Romacho, Tania; Martinez‐Tellez, Borja (Wiley, 2026)
Brown adipose tissue (BAT) is increasingly recognized as a metabolically active tissue in humans, although its physiological relevance remains incompletely understood. In rodents, BAT is well characterized, with interscapular BAT (iBAT) representing the main thermogenic depot. In contrast, the existence and persistence of iBAT in adult humans have long been overlooked. In this review, we synthesize anatomical, histological, imaging, and molecular evidence supporting the presence of a potentially active iBAT depot within the dorsocervical subcutaneous adipose tissue in humans. Gene expression and histological studies have conclusively identified dorsocervical subcutaneous adipose tissue as iBAT in human neonates. In adults, the persistence of this depot has been suggested by early histological observations, although definitive molecular confirmation is still lacking. More recent data from HIV-1-infected individuals report increased expression of BAT-related markers in the dorsocervical region; however, histological analyses have not consistently confirmed the presence of iBAT in this population. In parallel, two independent cold-induced 18F-FDG-PET/CT studies have reported elevated glucose uptake in this area, with a higher prevalence in women. Taken together, these findings suggest that a dorsocervical subcutaneous adipose depot with BAT-like characteristics may persist into adulthood, particularly in women. Nevertheless, targeted biopsy studies combined with molecular and cellular analyses, together with advanced PET-CT imaging using tracers capable of assessing thermogenic activity in vivo, are required to clarify whether this tissue represents classical BAT, a beige adipose depot, or a developmentally retained adipose niche. Defining the identity and function of this depot would advance current concepts of human adipose tissue heterogeneity.